Saudi Arabian Women’s Knowledge of Probiotics and Prebiotics - Alissa, Nawal (Progress in Nutrition, 2022)
Objectives: In view of the potential positive role of probiotics and prebiotics in prevention and management of various diseases, understanding the perceptions of probiotics/prebiotics and their benefits on health among Saudi Arabian women is important. The purpose of this study was to investigate the knowledge of probiotic and prebiotic among Saudi Arabian women. Methods: Participants were invited to complete an online survey to evaluate their knowledge about probiotic and prebiotic. The online survey was distributed via email and social media platforms. A total of 206 Saudi Arabian women responded to the survey. Results: Most of the participants were aged 18-25 years. The analysis of the responses’ level of knowledge resulted in a mean of 3.27 (between medium knowledge and good knowledge). Most of the participants were familiar with the definition, facts, and benefits of probiotic and prebiotic. The most recognized source of information about probiotic and prebiotic was books and studies. Conclusion: The overall level of knowledge of probiotic/prebiotic among Saudi Arabian women is slightly above average. Improved nutritional knowledge of Saudi Arabian women tasked with taking care of their own nutrition, and that of their families, has implications for the adoption of health eating patterns.